On the ‘burden’ of German unification - Jorg Bibow (PSL Quarterly Review, 2012)
This paper investigates the causes of western Germany's remarkably poor performance since 1992. It challenges the view that Germany's poor economic record and marked deterioration in public finances since unification might be largely attributable to that event. Instead, the analysis highlights that Germany's approach to macroeconomic policymaking has starkly conflicted with economic theory and best practice. Not the unification "shock" itself, but the ill-guided fiscal and monetary policies pursued since 1991 caused the severe and protracted de-stabilization of western Germany--and today's ongoing crisis.